CONTROL PASIV0 DE LA FORMACIÓN DE LOS TORBELLINOS DE LA CALLE VON-KÁRMÁN - Santa Cruz, A. (2004)
This study focuses on the flow modifications generated by a splitter plate placed downstrearn of a half cylinder compared to the wake formation without the plate. For moderate Reynolds numbers, spatial and temporal correlation coefficients calculated from velocity fields rneasured by Particle-lrnage-Velocímetry (PIV) are used to analyze the cornplex dynamics ofthe flows and to highlight vortex formation rnechanisms. Using this too!and t1ow visualization, the near wake structures are identified. Thus the interference of the shear !ayer with the stabilizer has a noticeable influence on the wake characteristics.